Periodic Modulations of Magnetostatic Field in Ferromagnetic Cylinder and Their Influence on Etching Figure Formation in Acid Solutions - Dzhezherya, Yu.I.; Gorobets, O.Yu.; Kuz, O.P.; Klymuk, O.S.; Gorobets, Yu.I. (Металлофизика и новейшие технологии, 2016)
Ordinary cylindrical specimens with easy-axis anisotropy perpendicular to the axis of a cylinder are studied. As shown, the inhomogeneous long-wave magnetic configurations of harmonic type can be created and observed in such samples. A linear theory is developed to simplify the set of Landau— Lifshitz and Maxwell’s equations to one general equation for a magnetostatic potential. The ranges of magnetic fields and the self-parameters responsible for the inhomogeneous periodic configuration formation are determined when solving a boundary value problem for a magnetostatic potential. Dependence of the period of magnetization wave on a magnetic field value, the constant of anisotropy and diameter of a cylinder is determined. The proposed theory gives qualitative explanation of the experiment when, using the Bitter’s powder-like figures’ method, quasi-periodic distributions of the magnetostatic fields can be observed in samples. These fields arise under external magnetic field of about 1 kOe directed along the axis of a steel cylinder and are absent without external magnetic field. An example of practical application of long-wave magnetic structures for a surface morphology control during chemical etching of ferromagnetic metals in acid solutions is given. The quasi-periodic structure of a corrosion surface of ferromagnetic cylinder corresponds to the period of a long-range magnetic structure.